The long-term effects of labor market entry in a recession: Evidence from the Asian financial crisis - Eleanor Jawon Choi; Jaewoo Choi; Hyelim Son (W.E. Upjohn Institute for Employment Research, 2019)
This paper investigates the long-term effects of initial labor market conditions by comparing cohorts who graduated from college before, during, and after the 1997-1998 Asian financial crisis. We measure the overall welfare impact by examining not only labor market activities but also family formation and wealth accumulation. Using data from 20 waves of the Korean Labor and Income Panel Study, we find a substantial and persistent reduction in employment, earnings, marriage, fertility, and financial assets among men who graduated in a bad economy. For women, limited job opportunities at graduation result in an increase in childbearing.
Keywords: E32; J10; E21; J20; J31; 330; recession; financial crisis; long-term effects; college graduates